Up, up, ever up! : Junko Tabei : a life in the mountains - Yasuda, Anita (Clarion Books, an imprint of HarperCollinsPublishers, 2024)
"Junko Tabei dreamed of a life climbing mountains. But men refused to climb with her. Sponsors told her to stay home. And gloves were not made to fit her hands. Junko, eager and unstoppable, wouldn't let these obstacles get in her way. Instead, she planned an expedition to summit Mount Everest with an all-women team. Battling icy peaks, deep crevasses, and even an avalanche, Junko refused to give up. She climbed step by step . . . up, up, ever up! After summiting the world's tallest peak, Junko took on a new challenge: protecting the wild spaces she loved for future generations. This gorgeously illustrated celebration of a trailblazing climber who shattered gender stereotypes invites us to dare to reach our dreams--no matter how big"--Front sleeve.